Fazer filosofia em um planeta ferido : whitehead, stengers e uma filosofia ambiental - Silva, Fernando Silva e (2022)
This dissertation aims to outline some of the fundamental terms for a philosophy in a wounded planet. That is, an environmental philosophy that, from metaphysics to politics, from epistemology to ethics, poses itself the problem of the diversity of modes of inhabiting the earth of humans and non humans, taking into account, first and foremost, the context of climate change and generalized ecological perturbation. In order to do so, I start from the thesis that the concept of nature—a collective creation of modern philosophy, science, and other practices of production of knowledge and truths—is the grounds for modes of inhabiting the earth that are colonizing and thin the world, that is, make it poorer, delegitimizing uncountable existences and experiences. In its place, I propose a notion of environment and other connected notions. The contributions of the philosophers Alfred North Whitehead and Isabelle Stengers are crucial to craft the terms and modes of thinking, feeling and imagining that compose this environmental philosophy. In the first chapter, I present some of the historical and conceptual challenges in conceiving a denatured environmental philosophy. In the next chapter, I introduce the whiteheadian concept of bifurcation of nature, which organizes his historical, philosophical approach to nature’s role in modernity. Chapter 3 proposes an environmental metaphysics, built upon Whitehead’s writings, which underlie this work’s environmental philosophy. The fourth chapter offers a complementary analysis of the workings of modern science and philosophy based on Stengers’ philosophy of science. In chapter 5, I show how Stengers’ concepts of ecology of practices and cosmopolitics are capable of approaching the conditions for the coexistence of modern practices of production of knowledge and truths with other practices, especially those called non modern. Chapter 6 indicates a series of ethical and political developments of the cosmopolitical proposal, while presenting the stengersian approach to contemporary climate change through the concept of intrusion of Gaia. In the last chapter, I indicate what the main elements of a philosophy in a wounded planet are. Firstly, I suggest a philosophical animism which reorganizes the environmental philosophy proposed in this dissertation. Secondly, I focus on how attention, care and uncommunity are central notions for the ethics and politics of the philosophy I seek. Finally, I sustain that caring for the planetary wound and the coming worlds depends on acknowledging the webs of mutual sustaining and requires rejecting the ways of inhabiting the earth that neglect the planet.